Milk extraction for human consumption from N'Dama cattle under village management conditions in The Gambia - Agyemang, K.; Jeannin, P.; Grieve, A.S.; Bah, M.L.; Dwinger, R.H. (1988)
Location performance of N’Dama cattle was recorded under village management conditions in four ecological variable villages in the Gambia. A total of 636 cows were recorded during the study. The highest daily milk offtake 1.7 kg/cow/day took place when cows were 4 – 6 weeks post-partum. Daily milk offtake was also influenced by month of extraction low in late dry season (0.8kg/cow/day) and increased sharply to 1.5kg at the beginning of the rainy season. The mean fat yield was 18.8 (s.d=6.4) kg with a coefficient of variation of 26.8%. Site and parity effects were significant on fat yield. Milk protein percent increased from a mean of 2.6% for cows in 1.6 weeks in lactation to a mean of 3.5 % for cows in the 50-54 weeks in lactation. The mean was also significantly affected by the season of calving. Milk offtake for human consumption was influenced by the stage of lactation and season. The overall mean lactation length is 346 days with 378.5 kg lactation milk offtake. The average calving interval is 18.5 months. In comparison of production parameters between twice and once-a-day milking situations, 12 month milk offtake (Mo) 430.0kg and 245.6 kg 12 month calf growth (CG) 60.0kg and 79.0kg, 12 month milk yield 910.0 kg and 877.0kg and calf mortality to 365 days 8.0% and 13.0% respectively were reported. The performance from N’Dama cattle in production systems under village management condition with minimal inputs was found remarkable.